A LOOK TO GRECO ROMAN ANTIQUITY: TO THINK THE MEANING OF PRAXIS AND LEXIS, WITH ARENDT (Argos, 2015)
A look to Greco Roman antiquity: to think the meaning of praxis and lexis, with Arendt This paper is about Hannah Arendt’s theory of action, as it is found in La condición Humana (The Human condition), a work from 1958. There, Arendt tries to recover the identity and meaning of the human action (praxis) as man’s activity qua man and as raw material of politics. In order to do it, she resorts to two fundamental experiences of western political culture: the Greek polis and the Roman res publica. The result is a theory of the action, which has been considered a great contribution to contemporary ethical political thought. We propose to focus our reflection on two historically forgotten aspects of human action, which Arendt manages to recover: the action as revelation and as enérgeia).
Keywords: action (praxis); discourse (lexis); public space; revelation; energeia